2011
DOI: 10.1007/s10237-011-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the porcine growth plate vary with developmental stage

Abstract: The objectives of this study were to extract the intrinsic mechanical properties of the growth plate at four different stages of growth and to compare two different methods of extracting these properties. Porcine distal ulnar growth plate samples were obtained from newborn, 4-, 8-, and 18-week (W) pigs and were tested using stress relaxation tests under unconfined compression. A four-parameter curve fitting procedure was developed to extract mechanical properties using the Transversely Isotropic Biphasic Elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Taken together, the results of our investigations suggest that the growth cartilage at the cranio‐proximal aspect of the secondary ossification centre in the lateral ridge of the equine femoral trochlea has a distinct matrix composition at birth. These subregional matrix variations may be associated with growth spurts and decrease the epiphyseal cartilage mechanical properties subregionally as recently illustrated in the ulnar physis of growing pigs . We speculate that a temporary focal weakening of the epiphyseal cartilage could predispose the vessels, housed within, to injury precipitating the early ischemic events of osteochondrosis.…”
Section: Discussionsupporting
confidence: 54%
“…Taken together, the results of our investigations suggest that the growth cartilage at the cranio‐proximal aspect of the secondary ossification centre in the lateral ridge of the equine femoral trochlea has a distinct matrix composition at birth. These subregional matrix variations may be associated with growth spurts and decrease the epiphyseal cartilage mechanical properties subregionally as recently illustrated in the ulnar physis of growing pigs . We speculate that a temporary focal weakening of the epiphyseal cartilage could predispose the vessels, housed within, to injury precipitating the early ischemic events of osteochondrosis.…”
Section: Discussionsupporting
confidence: 54%
“…We employed the method of maximum likelihood via a linear quadratic estimation (Kalman filter) algorithm to estimate the parameters in the transition model. This algorithm enables us to calculate the exact likelihood function, which includes the distribution of the first few observations of each donor [16-18]. As a result, the maximum likelihood estimation also includes the information of donors who have made fewer visits than the order of the transition model.…”
Section: Methodsmentioning
confidence: 99%
“…The application of epiphyseal displacement equivalent to 20% of the initial growth plate thickness was motivated by the need to obtain mesoscale values for Young’s modulus by simulating compression experiments on fully developed growth plate explants [ 37 ]. This prescribed displacement resulted in a 14.8% compressive growth plate strain across the combined layers of the reserve, proliferative and hypertrophic zones, which is representative of published explant growth plate experiments used for comparison ( Table 2 ) and other growth plate explant experiments [ 38 , 52 54 ]. Finite element simulations of rabbit experiments suggested that growth plate stresses reached values of 0.1 to 0.6 MPa in compression during activities such as sitting [ 18 ].…”
Section: Discussionmentioning
confidence: 77%